Tamaulipas: The profile of the new century - Pariente Fragoso, José Luis (Libros UAT, 2018)
The accelerated changes of today, both in the changes of work and in the professions themselves, force our university to put within reach of its students the necessary information that describes a true picture of the conditions in which Tamaulipas is located. and its development potential. Hence the need to have within the study programs common areas of initial training, to provide our students with those essential resources for their integral formation.